The Role of Socio-Cultural Factors (Cultural Values of Marriage and Perceived Social Support) in Partner Selection Criteria - Kheradmanesh, Behnaz; Mokhtari Masoumi Alamdarloo, Saeed; Mazaheri, Mohsen (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to examine the role of socio-cultural factors (cultural values of marriage and perceived social support) in the criteria for partner selection among students of Shiraz city. Methods: This research employed a descriptive and correlational design. The statistical population consisted of all students of Islamic Azad University, Shiraz branch, who were studying in the year 2022. A sample of 377 individuals (235 females and 142 males) was selected using a multi-stage cluster sampling method. The participants were assessed using the Marriage Cultural Values Questionnaire (Delkhomoush, 2013), the Multidimensional Perceived Social Support Scale (Zimet et al., 1988), and the Partner Selection Criteria Questionnaire (Schwartz & Hassebrook, 2012). After collection, the questionnaires were edited using SPSS software, and 26 items were analyzed at both descriptive and inferential levels. Findings: The analysis of the findings using multiple regression in a simultaneous method revealed that intellectual self-construal, emotional self-construal, hierarchical cultural values, and perceived social support significantly and positively influenced the partner selection criteria of the participants. Additionally, the results from the stepwise multiple regression analysis indicated that among the socio-cultural factors, intellectual self-construal had the most substantial role in partner selection criteria. Conclusion: Therefore, in the modern era, with the development of individuals’ socio-economic status, partner selection criteria have become more individualistic and oriented towards personal love and affection.